PENGARUH PAJAK PENGHASILAN BADAN TERHADAP PENERIMAAN PAJAK (STUDI KASUS PADA KPP PRATAMA SERPONG) - Budi, Saksono; Ajimat, Ajimat (CV. Pena Persada, 2019)
This study is to examine the effect of corporate income tax on tax receipts at the Serpong Pratama Tax Office. Data analysis was performed using a simple linear regression analysis method and product moment correlation. The calculation results show that there is an increase in the value of tax revenue in the Tax Office Pratama Serpong. Not only that, the calculation result of the t value is greater than the value of t table which indicates that the Corporate income tax has a positive effect on tax revenue at the Serpong pratama tax service office, thus the greater the corporate income tax, the greater the tax revenue at the tax office Serpong pratama. The value of r shows the number 0.965 with KD = 93.12% so it can be that the Corporate Income Tax has a positive correlation with Tax Revenue